Occupational class and risk of renal cell cancer. Issue 6 (16th May 2018) - Zaitsu, Masayoshi; Cuevas, Adolfo G.; Trudel‐Fitzgerald, Claudia; Takeuchi, Takumi; Kobayashi, Yasuki; Kawachi, Ichiro
Abstract: Objectives: We sought to examine the association between occupational class linked to job stress and the risk of renal cell cancer. To identify potential mediators, we additionally examined whether any observed associations persisted even after controlling for the contribution of stress‐related factors (eg, smoking, hypertension, and obesity). Methods: Using nationwide inpatient records (1984 to 2016) from the Rosai Hospital group in Japan, we identified 3316 cases of renal cell cancer (excluding upper tract urothelial cancer) and 168 418 controls. We classified patients' occupational class (blue‐collar workers, service workers, professionals, and managers) and cross‐classified it by industry type (blue‐collar, service, and white‐collar) based on a standardized national classification. Unconditional logistic regression with multiple imputation was used for the analyses. Results: A significantly elevated risk of renal cell cancer was found among men in higher occupational class (eg, professionals and managers). The elevated odds in male managers across all industries persisted even after controlling for smoking and alcohol consumption, with the association being more pronounced in blue‐collar industries (OR, 1.61; 95% CI, 1.34‐1.93). The association appeared to be mainly mediated by hypertension. Conclusion: Occupational class is associated with the risk of renal cell cancer in men, particularly through modifiable risk factors. Abstract : Objectives: We sought to examine the association between occupational class linked to job stress and the risk of renal cell cancer. To identify potential mediators, we additionally examined whether any observed associations persisted even after controlling for the contribution of stress‐related factors (eg, smoking, hypertension, and obesity). Methods: Using nationwide inpatient records (1984 to 2016) from the Rosai Hospital group in Japan, we identified 3316 cases of renal cell cancer (excluding upper tract urothelial cancer) and 168 418 controls. We classified patients' occupational class (blue‐collar workers, service workers, professionals, and managers) and cross‐classified it by industry type (blue‐collar, service, and white‐collar) based on a standardized national classification. Unconditional logistic regression with multiple imputation was used for the analyses. Results: A significantly elevated risk of renal cell cancer was found among men in higher occupational class (eg, professionals and managers). The elevated odds in male managers across all industries persisted even after controlling for smoking and alcohol consumption, with the association being more pronounced in blue‐collar industries (OR, 1.61; 95% CI, 1.34‐1.93). The association appeared to be mainly mediated by hypertension. Conclusion: Occupational class is associated with the risk of renal cell cancer in men, particularly through modifiable risk factors.